2021
DOI: 10.1016/j.jeconom.2020.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Consumer panic in the COVID-19 pandemic

Abstract: We develop an econometric model of consumer panic (or panic buying) during the COVID-19 pandemic. Using Google search data on relevant keywords, we construct a daily index of consumer panic for 54 countries from January to late April 2020. We also assemble data on government policy announcements and daily COVID-19 cases for all countries. Our panic index reveals widespread consumer panic in most countries, primarily during March, but with significant variation in the timing and severity of panic between countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 15 publications
3
129
0
1
Order By: Relevance
“…Finally, we found that after excluding the impact of social isolation, our model is still significant. This shows that although the government's isolation and restrictive policies can cause panic ( 53 ), they are not entirely responsible for causing panic, which is influenced by various factors. Future research may be carried out from the perspective of panic sources, such as the public, experts, and media, to explore the effects of these sources on panic-buying behavior, which will help to clarify the psychological mechanism of panic buying in more detail, and propose targeted strategies or policies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that after excluding the impact of social isolation, our model is still significant. This shows that although the government's isolation and restrictive policies can cause panic ( 53 ), they are not entirely responsible for causing panic, which is influenced by various factors. Future research may be carried out from the perspective of panic sources, such as the public, experts, and media, to explore the effects of these sources on panic-buying behavior, which will help to clarify the psychological mechanism of panic buying in more detail, and propose targeted strategies or policies.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived scarcity of resources and lack of access to them have both been linked with panic buying ( 13 , 21 , 66 ). This finding is consistent both with the psychological and social aspects of this model, in which the accumulation of objects symbolizes safety and security, as well as with the postulated evolutionary roots of hoarding and related behaviors ( 32 , 35 ).…”
Section: Research Findings Explained By the Integrated Modelmentioning
confidence: 99%
“…Panic buying, also referred to as “stockpiling,” is characterized by the purchase of “unusually large amounts of products,” in anticipation of or during a natural or man-made disaster, related to a fear of shortage of unavailability of the concerned products, which are usually food or hygiene-related items ( 10 , 11 ). Panic buying has been documented as a local response to phenomena such disease outbreaks or typhoons ( 12 , 13 ), but has occurred on an unprecedented scale in the context of COVID-19 and the attendant restrictions imposed in an attempt to contain the spread of the disease ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations